MUSEUM YANG INSTAGRAMABLE: Tinjauan Desain Interior yang Menjadi Tempat Favorit untuk Berfoto pada Museum De Tjolomadoe, Karanganyar - Yemima Nathania Santoso; sidhi pramudito (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
Instagram is a social media application that is very popular in this digital era. every photo or video that has been uploaded by the owner can describe what the account owner feels or experiences. From the photo or video hat have been uploaded, sometimes it can also be known what an individual or community is interested in at a certain time, which is often called something